The Manpower Aspect in the Field of Sports - Kiswandari, Melania (UI Scholars Hub, 2012)
As a result of enhanced professionalism and commercialization in the field of sports, it has become an industry of its own. Professionalism and industrialization are correlated; therefore sports actors’ performance achieved as a result of their professionalism lead to the commercialization, and even to the industrialization of certain (branches of) sports. On the other hand, it is considered that industrialization which involves the commercial aspect is able to maintain, and even enhance sports actors’ professionalism/performance. In practice, such correlation is not always directly proportional, but inversely proportional. There have been cases of issues related to sports actors’ welfare not being properly fulfilled, in fact, being far below the general manpower standards applicable to people doing work (workers/laborers). In general such cases include late or non-payment of wages, reducing bonuses, implementation of contract not accordance with the initial agreement, unilateral termination of contract without compensation for damages and others. The frequently arising question is whether sports actors, particularly athletes, have the status of ‘nonemployee’ professionals, or the status of ‘employees’. The various existing opinions related to such issue of status raise certain legal implications, particularly from the manpower aspect which emphasizes the welfare and legal protection of ‘workers’, which are also often experienced by athletes. It is expected that this article will be able to provide to the readers a broader view regarding the status of athletes’ ‘manpower’ status